PENGARUH KOMUNIKASI PENYULUHAN PT. JASA RAHARJA (PERSERO) CABANG RIAU TERHADAP TINGKAT KESADARAN MENGENAI ASURANSI KECELAKAAN PADA SISWA/I SMK MUHAMMADIYAH 2 KOTA PEKANBARU - Audilla, Deniesya Putri; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Counseling activities are still being carried out to convey information to the public so that the information conveyed can be known and utilized by the community. One of the counseling activities is about accident insurance delivered by PT. Jasa Raharja (Persero) Riau Branch to Students of Muhammadiayah Vocational High School 2 Pekanbaru so that they better understand the roles and functions of PT. Jasa Raharja (Persero) as an accident social insurance company.The purpose of this research is to find out whether there is an effect of counselling communication by PT. Jasa Raharja (Persero) Riau Branch on the level of awareness about accident insurance in students of SMK Muhammadiyah 2 Pekanbaru. The theory used in this research is AIDDA theory.This study uses quantitative research with explanatory methods. Data collection techniques in this study by distributing questionnaires to students of SMK Muhammadiyah 2 Pekanbaru who participated in counseling activities with a sample of 105 respondents who were determined through Proportional Stratified Sampling.The results show the value of regression coefficient in this study is Y = 18.000 + 0.472 (X). Meanwhile tcount (7.243)> ttable (1.983) with a significance level of 0.00 and smaller than α = 0.05. Based on the correlation interpretation guidelines, a correlation value (R) of 0.581 is obtained, thus the relationship between the communication variables of accident insurance counseling and the level of student awareness of SMK Muhammadiyah 2 Pekanbaru in the moderate category. Furthermore, the results of the determination test (R2) of 0.337. It can be explained that 33.7% of the level of student awareness of SMK Muhammadiyah 2 Pekanbaru is influenced by communication and the rest is influenced by other factors by 66.3%. Keyword: Counseling Communication, Accident Insurance, Awareness